Comparison of two referral strategies for diagnosis of axial spondyloarthritis: the Recognising and Diagnosing Ankylosing Spondylitis Reliably (RADAR) study. Issue 10 (13th October 2012) - Sieper, Joachim; Srinivasan, Shankar; Zamani, Omid; Mielants, Herman; Choquette, Denis; Pavelka, Karel; Loft, Anne Gitte; Géher, Pál; Danda, Debashish; Reitblat, Tatiana; Cantini, Fabrizio; Ancuta, Codrina; et al.
Abstract : Objective: To determine which of two referral strategies, when used by referring physicians for patients with chronic back pain (CBP), is superior for diagnosing axial spondyloarthritis (SpA) by rheumatologists across several countries. Methods: Primary care referral sites in 16 countries were randomised (1 : 1) to refer patients with CBP lasting >3 months and onset before age 45 years to a rheumatologist using either strategy 1 (any of inflammatory back pain (IBP), HLA-B27 or sacroiliitis on imaging) or strategy 2 (two of the following: IBP, HLA-B27, sacroiliitis, family history of axial SpA, good response to non-steroidal anti-inflammatory drugs, extra-articular manifestations). The rheumatologist established the diagnosis. The primary analysis compared the proportion of patients diagnosed with definite axial SpA by referral strategy. Results: Patients (N=1072) were referred by 278 sites to 64 rheumatologists: 504 patients by strategy 1 and 568 patients by strategy 2. Axial SpA was diagnosed in 35.6% and 39.8% of patients referred by these respective strategies (between-group difference 4.40%; 95% CI −7.09% to 15.89%; p=0.447). IBP was the most frequently used referral criterion (94.7% of cases), showing high concordance (85.4%) with rheumatologists' assessments, and having sensitivity and a negative predictive value of >85% but a positive predictive value and specificity of <50%. Combining IBP with other criteria (eg, sacroiliitis, HLA-B27) increased the likelihood for diagnosing axial SpA. Conclusions: A referral strategy based on three criteria leads to a diagnosis of axial SpA in approximately 35% of patients with CBP and is applicable across countries and geographical locales with presumably different levels of expertise in axial SpA.